Pengembangan Perangkat Pembelajaran dengan Model Problem Based Learning pada Topik Pecahan untuk Kelas III SD - Al Maqfiroh, Musafah; Amin, Siti Magfirotun; Nafiah, Nafiah; Hartatik, Sri (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
The background of this research is that there are still very few teachers who are not guided by learning tools and only refer to teacher and student books. This study aims to (1) describe the validity of learning tools using the problem-based learning model in learning mathematics on the topic of fractions in Class III SD (2) describe the feasibility of learning devices using the problem-based learning model in learning mathematics on the topic of fractions in Class III SD (3) analyze the effectiveness of learning tools with problem-based learning models in learning mathematics on the topic of fractions in Grade III SD. This research uses the type of development research with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of this study were 28 Class III students. This study uses evaluation sheet data sources and tests. Data collection techniques include validation questionnaires and tests. Analysis of the data used analysis of validity, feasibility, and validity. The validation results show the validity of lesson plans 4.74, Teaching Materials 4.6, LKPD 4.4, and Assessment Instruments 4.6 which meet the criteria of